The moderating effects of risk culture on the relationship between fraud risk management and the performance of banking sector in Nigeria - Umaru, Hussaini (2020)
Banks serve as an indispensable part of the financial system, performing a crucial role in intermediation which results in a flow of financial resources in an economy. However, the recurring nature of fraud has hindered the effective performance of banks in Nigeria. Fraud is considered as one of the most costly crimes in the business world that affects all types of business organizations. Every business transaction is exposed to the risk of fraud be it in the banking sector, insurance companies, private organizations, and government institutions. This has prompted regulatory authorities, experts and scholars to focus their attention on fraud risk management, which is a systematic mechanism and comprehensive tool to prevent, detect, and respond to fraud. This study examined the relationship between fraud risk management and bank performance and the moderating effect of risk culture on the relationship using Partial Least Squares Structural Equation Modelling (PLS-SEM). Data was collected from a field survey of risk experts from 366 listed banks in the Central Bank of Nigeria website. Of the 328 questionnaires that were returned, 305 were deemed usable for data analysis using PLS-SEM. The findings of the study revealed that fraud risk management and fraud risk management practices have positive and significant relationship with bank performance. It was further revealed that risk culture positively moderates the relationship between fraud risk management and bank performance. The research recommends strengthening fraud risk management by further investing in various fraud prevention, fraud detection and fraud response practices to improve bank’s performance. In addition, banks are recommended to invest in programs that inculcate risk culture in their daily operations as strong risk cultures improves the effect of risk management practices on bank’s performance. This study benefits investors, policy makers, regulators and government concerning the effects of fraud risk management and risk culture on the performance of banks in Nigeria.